Mister Magic : a novel - White, Kiersten (New York : Del Rey, 2023)
Reuniting 30 years after a tragic accident ended their show Mister Magic, the five surviving cast members, who hold the secret of their close circle, the mystery of the beloved magical host and what really happened on that deadly last day, soon wonder if they've been lured into a trap.
Keywords: Children's television programs -- Fiction; Child actors -- Fiction; Reunions -- Fiction; Podcasts -- Fiction; Thrillers (Fiction); Paranormal fiction